A narrative review of alcohol control policies in Latvia between 1990 and 2020. (27th March 2023) - Gobiņa, Inese; Isajeva, Laura; Spriņģe, Lauma; Vrobļevska, Elīna; Pelne, Aija; Mārtiņsone, Una; Lange, Shannon
Abstract: Issues: Latvia has one of the highest alcohol per capita consumption in Europe. This study provides a narrative review of all evidence‐based population‐level alcohol control policies implemented in Latvia during the past 30 years. Approach: A review of country‐level alcohol control policies implemented in Latvia between 1990 and 2020 was conducted. The World Health Organization's "best buys" and other recommended interventions for alcohol control were used to guide the search. Key Findings: Alcohol control policies in Latvia have evolved significantly over the last three decades. The most changes to alcohol control policy occurred in the transitional period between regaining independence in 1991 and joining the European Union in 2004. A number of significant alcohol control policies have been implemented to reduce alcohol availability and affordability, to restrict alcohol marketing and to counter drunk‐driving. However, since 2010, when an increasing trend of alcohol consumption was observed, there has been a reluctance to pursue national public health policy actions to reduce alcohol consumption, and few adjustments to legislation to increase alcohol control have been made. Implications: Despite the progress in alcohol control, Latvia still has considerable potential for strengthening alcohol control to reduce the high levels of alcohol consumption. Conclusion: Although several alcohol control policies have been established in Latvia, many of the planned activities to limit alcohol intake and related harm have not been executed. Public health goals rather than political and economic incentives should be prioritised to reduce high levels of alcohol consumption in Latvia.